Throwing velocity and efficacy during water polo matches - Abraldes, J. A.; Vila, H.; Ferragut, C.; Rodriguez, N.; Fernandes, R. (The Open Sports Sciences Journal, 2012)
Our objective was to assess throwing frequency, velocity, place of execution and efficacy during an European Water Polo Championship. The playing field was divided in five zones (1 to 5) based on the distance from goal: 0-2m, 2- 5m, 5m to midfield, over midfield and penalty mark, and the throwing velocity was assessed using a radar (frequency of 100Hz and sensitivity of 0.045m·s-1). After a descriptive analysis, differences in throwing velocity between throwing zones were tested using a repeated measures ANOVA (with the Bonferroni post-hoc test), and differences between genders and goal/no goal situations were obtained using an independent measures T-Test (p<0.05). Results showed that ~93% of the throws were made from the 2m and the middle field lines, and that the highest throwing velocities were obtained from the penalty mark. Female and male players presented higher throwing velocities in the most remote areas compared to those closest to the goal. When genders were compared, female players evidence lower throwing velocity in all field zones compared to male counterparts, with the exception of zone 1. This is observable also when considering throwing efficacy, once it occurs in each field zone in both goal and no goal conditions. When analysing the throwing velocity by field zones regarding throwing efficacy, in general no significant differences were found between the goalscoring shots and the non-scoring shots (for both genders), excepting the zone 3 for the total sample, in which higher values when scoring were observed. Future studies should analyse the specific player positions and focus on World Wide tournaments.